2021
DOI: 10.1007/s10811-021-02462-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen limitation on growth, biochemical composition, and cell ultrastructure of the microalga Picocystis salinarum

Abstract: In recent years, biodiesel production has attracted worldwide attention due to the awareness of fossil fuel depletion, and microalgae biomass is considered a promising raw material for its formulation. The present study evaluated the effects of different levels of nitrogen limitation (37.5, 18.75, 9.375 mg L -1 NaNO 3 ) on the growth, cell ultrastructure and biochemical composition of Picocystis salinarum as a potential raw material source for biodiesel. During a culture period of 20 days, the growth measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 50 publications
2
3
0
Order By: Relevance
“…Nitrogen is an indispensable part of each polypeptide in protein structures 21,33 . A dramatic increase in protein levels with high nitrate concentration was expected, yet we observed a minimal change in both soluble and insoluble protein levels with different nitrate in the medium, similar to the previous observation made by Tarazona et al, (2021) 25 . Araújo and Garcia (2005) 34 found the protein content to be unaffected at lower temperatures (20 °C and 25 °C) compared to high temperatures (30 °C) in the diatom Chaetoceros cf.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Nitrogen is an indispensable part of each polypeptide in protein structures 21,33 . A dramatic increase in protein levels with high nitrate concentration was expected, yet we observed a minimal change in both soluble and insoluble protein levels with different nitrate in the medium, similar to the previous observation made by Tarazona et al, (2021) 25 . Araújo and Garcia (2005) 34 found the protein content to be unaffected at lower temperatures (20 °C and 25 °C) compared to high temperatures (30 °C) in the diatom Chaetoceros cf.…”
Section: Discussionsupporting
confidence: 92%
“…With nitrate concentration, heatwaves synergistically increased both the soluble and insoluble sugar in microalgae. Similar to our study, Juneja et al, (2013) 25 also found an increase in sucrose (57%) in microalgae when exposed to 38 °C. The high sugar levels in microalgae during the heatwaves may help herbivores to fulfill the higher energy demand at higher temperatures 32 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Krienitz et al (2012) states that "Picocystis salinarum from saline inland waters represents a link between marine and freshwater habitats from both an ecological and a phylogenetic point of view and is therefore of great interest. " Also, recent reports have suggested that Picocystis may have potential biotechnological applications from wastewater treatment (Ali et al, 2017;Ouada et al, 2018), to biofuel production (Wang et al, 2014;Delgado et al, 2021). In spite of demonstrating such unique environmental adaptations, flourishing and out competing other primary producers at extreme salinities and influencing the food web dynamics (Krienitz and Kotut, 2010), P. salinarum has gone unreported in most of the culture independent metagenomic studies of saline ecosystems all over, indicating the lack of information about this organism on molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, microalgae have emerged as a potential source for biodiesel production. In recent years, they have been considered as a third-generation biofuel feedstock that may replace traditional fossil fuels [13]. The use of microalgal biomass for biodiesel production is eco-friendly and sustainable.…”
Section: Introductionmentioning
confidence: 99%